Identifikasi Strategic Planning dengan Implementasi Metode SWOT dan BCS pada UMKM Mesthi Cafe - Deviyanti, I Gusti Ayu Sri; Fais, Moh. Ainul; Mohamad, Silvana; Widari, Nyoman Sri (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2024)
The development of MSMEs in Indonesia is very rapid, especially in the food business. Even so, there are also many people who are running a food business out of business because of the many competitors. Therefore, a solution is needed so that the food business continues to run. One way is to use the concept of strategic planning aspects from internal and external with the SWOT method, and conduct a performance appraisal of company executives to sharpen strategies and initiatives that can be achievedKeywords: BCS, Strategic Planning, SWOT